MicroRNA from bench to bedside - Xiao, Junjie (Academic Press, 2022)
MicroRNA: From Bench to Bedside provides an in-depth, expansive overview of microRNA from fundamentals to clinical practice. It presents researchers with detailed insights on the topic of microRNA, exploring foundational knowledge that is followed by methodologies and the latest technologies for research and potential theragnostic and therapeutic applications for specific diseases. The book consists of eight parts, beginning with an introduction to microRNA and the current state of the field, followed by sections on biogenesis and maturation of microRNA, and methodology and bioinformatics, where chapters focus on isolation and detection techniques. Sections then move on to molecular mechanisms and gene regulation, considering topics such as transcriptional regulation and epigenetic regulation, as well as the role of microRNA as biomarkers. Additionally, microRNA and human disease and microRNA-based therapeutics are explored, focusing on a wide range of diseases such as cancer, age-related disease, cardiovascular disease, microRNA targeted therapy in hepatitis and therapeutic strategies for diabetes. The book concludes with a discussion on advances and future perspectives in microRNA investigation. Covers the topic of microRNA in detail, from foundational knowledge to clinical application Explores the physiological and pathological roles of microRNAs in various human diseases, including neurological, cardiovascular and age-related diseases Discusses future directions and challenges in the field Includes chapters on methodology and bioinformatics for microRNA research--